ASSESSMENT OF HEAVY METALS IN FISH AND SEDIMENTS FROM RIVER MTAKUJA IN THE VICINITY OF A GOLD MINE IN TANZANIA - Panga, Victor A.; Kumwenda, Mwingereza J.; Makundi, Ismael N. (Bulletin of Natural Sciences Research, 2023)
Concentrations of heavy metals namely Cr, Fe, Cu, Zn, As, Cd and Pb in African Sharptooth Catfish (clarias gariepinus) and sediment from river Mtakuja Tanzania were analyzed using the Energy Dispersive X-ray Fluorescence spectrometry technique. 32 samples from fish and sediment were investigated. The results show that the concentration of heavy metals was higher in upstream areas than in the downstream area. The concentration of Fe of 428.5 mg/kg in catfish from the upstream area was about 2 times 243.8 mg/kg obtained from the same fish in the downstream area. Similar cases observed for sediments with Fe concentration of 127626.9 mg/kg from upstream that was about 6 times higher than that of 21460.3 mg/kg from downstream area. The concentration of 44.8 mg/kg for Cu in the upstream area sediment was also about 2 times higher than 23.2 mg/kg in the downstream area sediment, while for as the concentration of 13.2 mg/kg was measured in the upstream, which is which is more than 5 times 2.5 mg/kg measured in downstream. The concentration of Cr in the catfish was 17.6 mg/kg which is higher than the permissible limit values of 0.8 mg/kg set by the European Commission (EC), 0.2 mg/kg set by the Food and Agricultural Organization (FAO) and 0.15 mg/kg the World Health Organization (WHO) limit. Moreover, the concentration of Cd was 3.0 mg/kg, which is above the permissible level of 0.2 mg/kg recommended by the EC and WHO. A positive correlation exists between the Cu, Pb, Fe and Cd concentration found in sediments and fish samples. The results show that the river Mtakuja is polluted by mining waste, domestic and agrochemical activities. This suggest that, there is a need for regular monitoring of heavy metal in river Mtakuja in order to monitor and protect aquatic organisms and health of benefactors of this river.
Keywords: Heavy metals; Energy Dispersive X-ray Fluorescence; African Sharptooth Catfish; Gold mine